Bond behavior of FRP carbon plates externally bonded over steel and concrete elements: Experimental outcomes and numerical investigations. (1st May 2016) - Ceroni, F.; Ianniciello, M.; Pecce, M.
Abstract: The paper is firstly aimed to furnish a review of the current knowledge about the bond behavior of Fiber Reinforced Plastic (FRP)-steel joints with reference to: a) experimental results of bond tests available in the technical literature, and b) existing strength model for estimating the debonding load. In order to assess the influence of geometrical and mechanical properties of the adhesive on the debonding load, parametric analyses have been carried out by means of some selected bond strength models. The effectiveness of these models has been also checked by means of comparisons with experimental debonding loads collected from technical literature. The second objective of the paper is the comparison of the bond behavior of FRP-steel and FRP-concrete joints in order to identify the role of the adhesive on the bond behavior separately from the concrete. The comparison is aimed to assess bond laws for FRP-concrete joints taking into account the only nonlinearities of the adhesive and to model the concrete as a nonlinear material. To this purpose few experimental bond tests were carried out by the Authors on carbon FRP plates bonded over both steel and concrete support according to the same lay-out and set-up. Finally, basing on the experimental bond law assessed for the FRP-steel joints, a Finite Element (FE) plane model with interface elements is developed for validating the experimental results of bond tests.